, ; Influencing factors of profit and profitability of agricultural large firms in the Omsk region, Russia - Eberhard Schulze; Peter Tillack; Oleg Patlassov (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2002)
40 . , : , , , . . - . 2000 2,0 %; 6,4 %; -9,8 %, -16,0 %. , , , . (-16 %), , , - . , , , , : 26,4 %; 31,8 %; 11,8 %; 4,1 %. , , , . , . , , . . , , . , . – – The discussion paper 40 represents the results of an analysis for determining influencing factors on profits and profitability of Russian enterprises in the region of Omsk. Based on the final yearly reports of the enterprises it is shown, that in Russia five earning ratios can be distinguished: the gross profit, the profit on sales, the profit before taxes, the profit on ordinary activity, and the net profit. The gross profit and the profit on sales are similar for all tested enterprises. Therefore, in this article only the gross profit, or the profitability of the gross profit are discussed. For the year 2000, the average profitability of the gross profit of the examined enterprises amounted to 2,0 %. The profitability on the basis of the profit before taxes was 6,4 %, the profitability of the profit on ordinary activity -9,8 %, and the profitability of the net profit amounted to -16,0 %. When compared with the profit before taxes, the reduced profit on ordinary activity is caused by taxes and similar tributes which are notably higher than the governmental subsidies granted to the enterprises. The extremely low profitability rate of -16 % based on the net profit is additionally influenced by extraordinary tributes, caused by locusts in this case. However, if the enterprises would not have costs for supporting the households, and if the government would assume the costs for the social infrastructure of the village, a duty it is in charge of by law, all four earning ratios would be positive: 26,4 %; 31,8 %; 11,8 %; 4,1 % respectively. The regression analyses show that the earning and the profitability ratios are positively influenced by the material factors fuel consumption, number of cows and milking performance per cow and year. In contrast, the number of tractors and, for net profit, the number of permanent employees have a negative effect on these parameters. The regression analyses based on financial factors demonstrate the significant positive or respectively negative influence of the proceeds and the costs. Furthermore, there are veritable positive effects of subsidies and negative influences of taxes and extraordinary tributes. Detailed consideration of costs shows that material usage have positive, and amortisation and remuneration of work negative effects. As particularly shown by the factor and cluster analyses, the profits decline with increasing grassland and forest area.
urn:nbn:de:gbv:3:2-23056
Keywords: Q13; Q47; 330; Large-scale Farms; profitability; debts; Landwirtschaft; Großunternehmen; Gewinn; Rentabilität; Schätzung; Russland; Omsk (Oblast)